The Challenges of Spreading Disinformation (Hoax) Related to Aviation Safety on Social Media and Efforts to Strengthen the Value of National Unity - Hairul Amren S; Ahmad Fakhrizal Pulungan; Daffa Hamonangan Hasibuan; Dicki Azly Asfa; M.Rafi Erwino; Wahyu Kurniawan (International Journal of Society and Law, 2026)
This study discusses the challenges of spreading disinformation (hoaxes) related to aviation safety on social media and mitigation efforts that at the same time strengthen the value of national unity. The approach used is qualitative-descriptive through literature study, content analysis of hoax narrative patterns, and conceptual analysis to formulate reinforcement strategies. The results of the study show that aviation safety hoaxes are generally in the form of false accident claims, reuse of old content claimed as new events, visual/audio manipulation, conspiracy theories, passenger safety procedural hoaxes, and sheep fighting narratives that trigger stigma. Factors driving the spread include emotional appeal (fear, surprise, anger), pseudo-credibility (expert/insider claims), information vacuum in the early phases of the incident, clickbait economic incentives, and polarization and low trust in institutions. The impact includes safety risks (e.g. following the wrong procedures), public panic and anxiety, decreased trust in regulators and operators, and disruptions to social cohesion that threaten the unity of the nation. Research recommends strengthening fast, accurate, consistent, and empathetic risk communication; digital literacy based on national values; multi-stakeholder collaboration between authorities, platforms, media, communities, and the public; as well as prevention strategies such as prebunking so that the public is better prepared to recognize hoax patterns from the beginning.